FROM CHAMPIONS TO CRISIS: COMMUNICATION MANAGEMENT AND LEADERSHIP TRANSITION IN ROMANIAN FOOTBALL - NEMEȘ, Diana-Ioana; IRIMIEȘ, Cosmin-Vasile; IRIMIEȘ, Laura-Maria; RAȚIU, Oana (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2025)
Introduction: Crisis communication has become a central element of contemporary sports, where reputation and stakeholder trust are as fragile as athletic performance. The study focuses on FC Farul Constanța, a Romanian football club that experienced a rapid shift from national champion in 2023 to play-out participant in 2024, followed by a leadership transition in 2025, when Gheorghe Hagi stepped down as head coach to assume an administrative role. Objective: The research aimed to examine how the performance crisis of Farul Constanța was communicated publicly and how Gheorghe Hagi’s personal brand influenced the perception of institutional stability during this period. Material and Methods: A qualitative case study approach was used, applying thematic content and discourse analysis to 85 public materials, including official club releases, media interviews, and social media posts from May 2023 to June 2025. The analytical framework was based on Coombs’ Situational Crisis Communication Theory (SCCT) and personal branding principles. Results: Findings indicate that Farul’s communication strategy relied heavily on Hagi’s symbolic capital, combining emotional cohesion with limited strategic diversification. Public messaging oscillated between defensive justification and reaffirmation of identity values. Discussion: The study highlights the vulnerability of sports institutions dependent on charismatic leaders, where the overlap between personal and organizational reputation can both stabilize and constrain crisis management. Conclusions: Sustainable resilience in sports communication requires balancing individual charisma with institutional transparency and structured communication strategies, ensuring long-term trust and brand coherence.